An AlGaAs/GaAs‐based planar Gunn diode oscillator with a fundamental frequency operation of 120 GHz. Issue 10 (October 2014) - Maricar, Mohamed Ismaeel; Glover, James; Khalid, Ata; Li, Chong; Evans, Gwynne; Cumming, David S. R.; Oxley, Christopher H.
ABSTRACT This letter reports the highest fundamental oscillator operating frequency of 120 GHz for gallium arsenide (GaAs)‐based Gunn diode. The letter describes the design, fabrication, and test of the aluminum gallium arsenide (AlGaAs)/(GaAs) planar Gunn diode with an anode to cathode separation of 1 μm and channel width of 120 μm. The planar Gunn diode was designed with an integrated series inductor in coplanar waveguide format. The experimental results showed that the planar Gunn diode oscillated at a fundamental frequency of 120.47 GHz with an RF output power −9.14 dBm. This is highest fundamental frequency and power recorded for a GaAs‐based Gunn diode. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2449–2451, 2014